2009
DOI: 10.1161/strokeaha.109.555953
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Thrombolysis in Stroke Attributable to Cervical Artery Dissection

Abstract: Background and Purpose-Intravenous thrombolysis (IVT) for stroke seems to be beneficial independent of the underlying etiology. Whether this is also true for cervical artery dissection (CAD) is addressed in this study. Methods-We used the Swiss IVT databank to compare outcome and complications of IVT-treated patients with CAD with IVT-treated patients with other etiologies (non-CAD patients). Main outcome and complication measures were favorable 3-month outcome, intracranial cerebral hemorrhage, and recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 30 publications
(26 reference statements)
5
87
0
6
Order By: Relevance
“…13,14 Local study investigators completed the forms systematically using prospectively ascertained in-hospital IV ischemic stroke thrombolysis registries. Completed forms from all centers were compiled in the coordinating center Basel, where the analysis of the pooled data was performed, as described previously.…”
mentioning
confidence: 99%
“…13,14 Local study investigators completed the forms systematically using prospectively ascertained in-hospital IV ischemic stroke thrombolysis registries. Completed forms from all centers were compiled in the coordinating center Basel, where the analysis of the pooled data was performed, as described previously.…”
mentioning
confidence: 99%
“…It represents up to 20%-25% of stroke etiology in young adults 1 and is the most common cause in patients younger than 55 years of age. ICD is the consequence of a mural hematoma in the arterial wall, with separation of the intima from the media.…”
mentioning
confidence: 99%
“…3,4 Intravenous thrombolysis (IVT) 5 is associated with poor recanalization rates and poor clinical outcomes. 1,3 Several published series have reported very low recanalization rates in tandem occlusions, from 8% to 9% during the first 2 hours 6,7 after thrombolytic drug infusion to 31% in the next 24 -72 hours. 4 Endovascular treatment is now increasingly considered and performed, especially following the results from randomized controlled trials ( [8][9][10][11][12] which demonstrated the superiority of combined strategies versus stand-alone intravenous treatments in large-vessel occlusion stroke.…”
mentioning
confidence: 99%
“…Trombolitik tedavinin mural hematomun büyümesine veya yalancı lumen içindeki trombüsün kopması ile emboliye neden olabilme risklerine karşın bu tedavinin seçilmiş vakalarda, güvenle kullanılabileceği de vurgulanmaktadır (40,41). Disseksiyon vakalarında görülen psödoanevrizmaların çoğunlukla benign seyirli olduğu kabul edilmektedir.…”
Section: Rekürrensunclassified